Analysis of The Impact of E-Learning on Fifth Grade Students - Aji Wicaksana; Ferina Agustini; Aries Tika Damayani (Universitas Pendidikan Ganesha, 2021)
When implementing E-learning, the teacher does not meet face to face with students, even though the role of the teacher in schools is very important in addition to teaching and educating students. It causes E-learning to have various impacts, both negative and positive impacts. This study aimed to analyze E-learning learning in fifth-grade elementary school students. This type of research was qualitative research. The techniques used to collect data were observation, interviews, questionnaires, and documentation. The instrument used to analyze the data was a questionnaire. The technique used in analyzing the data was descriptive qualitative. The data analysis technique in this study used three data acquisition procedures, namely data reduction, data presentation, and data verification. The result of the research is that E-learning can increase students' motivation and interest in learning more actively. E-learning is more flexible and can be accessed from anywhere. Can make students more independent in solving problems. The obstacle faced by students is the lack of supporting technology facilities for this learning process, such as the quality of gadgets and signals in the area around the school.